RETROPUBIC PROSTATECTOMY IN 96 PATIENTS IN SOBA UNIVERSITY HOSPITAL - Mahjoub Taha, Sami; Sharfee, Abd ElRaouf; Mustafa, Gamal (Gezira Journal of Health Sciences; Vol 7 No 1 (2011), 2011)
Background : Retropubic prostatectomy(RPP), is a good treatment option for  men with symptomatic bladder outlet obstruction caused by large size prostate. Objective : To determine the intraoperative, early and late postoperative complications of retropubic prostatectomy. Methods : This is a retrospective, small-scale hospital based study conducted in Soba University Hospital, Sudan. We include 96 patients, from Jan 2003 to Jan 2008 who underwent RPP. Results: The mortality rate was zero. Retrograde ejaculation in 50.1% , clot retention due to catheter block in 36.5% and transient urinary incontinence in 24%,  all were improved within the first three months postoperatively and intraoperative bleeding was reported in 9 patients (10%). Erectile dysfunction in 7.5% , wound  infection in 6.3% , urethral stricture  in 5.2% ,urine leakage in  4.2% and injury to adjacent  structures(peritoneum–bowel) was not reported.  Conclusion : The complications of retropubic prostatectomy  in Soba Hospital was found to be comparable to the literature.